Karakteristik Komposit Serbuk Kayu Jati Dengan Fraksi Volume 25%, 30%, 35% Terhadap Uji Bending, Uji Tarik Dan Daya Serap Bunyi Untuk Dinding Peredam Suara - Krisdianto, Andi, Wijianto, ST, M.Eng, Sc, Pramuko IP, Ir, MT (2016)
Purpose of the research is to know tensile strength and bending strength of teakwood dust composite with volume fractions of 25%, 30% and 35% according to ASTM D 3039-00 standards and ASTM D 790-99 standards and to know capacity value of sound absorption with sponge and plywood linings according to ANSI S1 13-05 standards. Primary material of the research is teakwood sawdust with matrix of Fox PVAc adhesive substance. Main variable of the research is fractions of sawdust volume of 25%, 30% and 35% with procedures of the tensile strength is referred to ASTM D 3039-00, the bending strength is referred to ASTM D 790-99 and test of sound absorption is referred to ANSI S1. 13-05. Results of the research showed that the highest average tensile strength of 1.95 Mpa was found at volume fraction of 25% and modulus of elasticity of 20.23 Mpa, whereas the lowest tensile strength of 1.03 Mpa was found at volume fraction of 35% and modulus of elasticity of 20.23 Mpa. The highest bending strength of 11.98 Mpa was found at 25% and modulus of elasticity of 112.73, whereas the lowest bending strength of 9.46 Mpa was found at volume fraction of 35% and modulus of elasticity of 74.22 Mpa. The highest value of the sound absorption without sponge and plywood linings was found at volume fraction of 35%, namely 2.36 dB, whereas the lowest one of 0.90 dB was found at volume fraction of 25%. The highest value of sound absorption with sponge and plywood linings was found at volume fraction 35%, namely 2.07 dB and the lowest one was found at volume fraction 25%, namely 1.05 dB,